A Study on EFL Teacher Strategies in Utilizing ICT for Regional Public Highschool of Indonesia - Kibar, Andi Halima; Ampa, Andi Tenri; Nappu, Syamsiarna (Tamaddun Life, 2023)
This mixed-methods study investigates the strategies employed by EFL teachers in integrating Information and Communication Technology (ICT) into their teaching practices within a regional public high school in Indonesia. By employing a combination of qualitative and quantitative data collection methods, the study draws upon a sample of teachers' perspectives via structured interviews and questionnaire responses. The English teachers of SMA Negeri 1 Maros were involved as the subject of the Research. The findings reveal that teachers utilize a range of ICT tools, such as LCD/LED projectors, PowerPoint presentations, audio-visual technologies, and radio broadcasts, with the primary aim of enhancing teaching efficacy and student engagement. The data suggests that the use of ICT significantly influences student comprehension and learning outcomes, with pupils demonstrating an accelerated understanding of material when taught via ICT-based methodologies. Therefore, the study provides valuable insights into the role of ICT in English language teaching in Indonesia, particularly shedding light on teachers' ICT utilization strategies and the impacts on student learning outcomes. These findings may inform future policy and practice in education, potentially guiding initiatives for ICT integration in the wider context of language education.